Powering Environmental Monitoring Systems in Arctic Regions: A Simulation Study - Prauzek, M.; Musilek, P.; Watts, A. G.; Michalikova, M. (Elektronika ir Elektrotechnika, 2014)
This paper describes a long-term simulation of an environmental monitoring system. This innovative approach combines harvesting-aware power management with primary batteries used as a back-up. It significantly extends the operational life of the device, while avoiding loss of data due to insufficient solar energy during winter in the harsh Arctic environment. The simulation considers the device to be located in the Arctic environment. Its main operation modes involve measurement from sensor interface, data storage and transmission. To perform an effective data-for-energy exchange, the device is controlled by a fuzzy energy management strategy. The new structure of the fuzzy rule-based system independently controls two separate variables related to data collection and the operation of a data buffer. The simulator uses meteorological data from Inuvik, Northwest Territories, Canada, to estimate the amount of energy available for solar harvesting. This site, located above the polar circle, receives very limited amounts of solar radiation during winter. Operation of the device is evaluated over a two-year period. The simulation results are described both numerically and using time-series plots of energy- and data-related variables. The performance is adequate for unsupervised operation of the system with annual maintenance visits to replace batteries. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.8020